Shallow-water Trapezioidea (Decapoda: Brachyura) from the South China Sea, including two new records, and notes on Tetralia glaberrima Herbst, 1790 - Sun, Yu-Li; Jiang, Wei; Sha, Zhong-Li (Zootaxa, 2024)
A collection of coral symbiotic crabs (Trapezioidea) from the South China Sea reports a total of 24 species, including 12 species of Trapeziidae (including one new record: Trapezia plana Ward, 1941), four species of Domeciidae, and eight species of Tetraliidae (including one new record: Tetralia brengelae Trautwein, 2007). Live color and mitochondrial cytochrome oxidase I (COI) sequence data of all species are provided.